Discordant Lifestyle Mobilities in East Asia: Privilege and Precarity of British Retirement in Thailand. Issue 5 (19th January 2016) - Botterill, Kate
ABSTRACT: This paper explores the lifestyle mobilities of British retirees in Thailand, drawing on empirical research conducted in 2012. Thailand is a host to a significant number of British retirees motivated by a search for a better lifestyle in Asia. This pursuit of mobility for lifestyle reasons, rather than economic gain or work, implies a relative privilege involving a range of choices and opportunities. For many, the lifestyle achieved in Thailand is perceived as mediating negative effects of ageing and enhancing well‐being. However, the material challenges of lifestyle mobility in Thailand, such as frozen pensions, healthcare costs and property insecurity, destabilise an initial optimism and lead to feelings of entrapment and immobility in relation to state policy and practice. The paper argues for a relational framing of lifestyle mobility as a means of understanding and analysing the differential experience of privilege and precarity in semi‐colonial or post‐colonial locations. Copyright © 2016 John Wiley & Sons, Ltd.